Associations of neighborhood environmental attributes with adults' objectively-assessed sedentary time: IPEN adult multi-country study - Owen, Neville; Sugiyama, Takemi; Koohsari, Mohammad Javad; De Bourdeaudhuij, Ilse; Hadgraft, Nyssa; Oyeyemi, Adewale; Aguinaga-Ontoso, Ines; Mitáš, Josef; Troelsen, Jens; Davey, Rachel; Schofield, Grant; Cain, Kelli L; et al. (Preventive medicine, 2018)
Neighborhood environmental attributes have been found to be associated with residents' time spent walking and in physical activity, in studies from single countries and in multiple-country investigations. There are, however, mixed findings on such environmental relationships with sedentary (sitting) time, which primarily have used evidence derived from single-country investigations with self-reported behavioral outcome measures. We examined potential relationships of neighborhood environmental attributes with objectively-assessed sedentary time using data from 5712 adults recruited from higher and lower socio-economic status neighborhoods in 12 sites in 10 countries, between 2002 and 2011. Ten perceived neighborhood attributes, derived from an internationally-validated scale, were assessed by questionnaire. Sedentary time was derived from hip-worn accelerometer data. Associations of individual environmental attributes and a composite environmental index with sedentary time were estimated using generalized additive mixed models. In fully adjusted models, higher street connectivity was significantly related to lower sedentary time. Residential density, pedestrian infrastructure and safety, and lack of barriers to walking were related to higher sedentary time. Aesthetics and safety from crime were related to less sedentary time in women only. The predicted difference in sedentary time between those with the minimum versus maximum composite environmental index values was 71 min/day. Overall, certain built environment attributes, including street connectivity, land use mix and aesthetics were found to be related to sedentary behavior in both expected and unexpected directions. Further research using context-specific measures of sedentary time is required to improve understanding of the potential role of built environment characteristics as influences on adults' sedentary behavior.
Keywords: Young Adult; Sedentary Behavior; Cross-Sectional Studies; Male; zpráva o sobě; Walking; mladý dospělý; Built environment; celosvětové zdraví; Adult; akcelerometrie; Aged; dospělí; Adults; mužské pohlaví; senioři; Exercise; průzkumy a dotazníky; chůze; Residence Characteristics; Global Health; Time Factors; senioři nad 80 let; Sitting time; lidé; sedavý životní styl; ženské pohlaví; Humans; Self Report; časové faktory; průřezové studie; Aged, 80 and over; Built Environment; Accelerometry; vytvořené prostředí; Female; Surveys and Questionnaires; cvičení; lidé středního věku; Sedentary behavior; charakteristiky bydlení; Middle Aged